Perifolliculitis capitis abscedens et suffodiens treatment with tumor necrosis factor inhibitors: A case report and review of published cases. Issue 9 (4th July 2019) - Takahashi, Toshiya; Yamasaki, Kenshi; Terui, Hitoshi; Omori, Ryoko; Tsuchiyama, Kenichiro; Fujimura, Taku; Aiba, Setsuya
Abstract: Perifolliculitis capitis abscedens et suffodiens (PCAS) or dissecting cellulitis is a rare condition presenting deep follicular occlusions, follicular ruptures and follicular infections in the scalp area with unknown etiology, which consequently cause primary neutrophilic cicatricial alopecia by the repeated follicular inflammation. PCAS is categorized as one of the "follicular occlusion tetrad" along with hidradenitis suppurativa, acne conglobata and pilonidal cyst. In the pathogenesis of the follicular occlusion tetrad, the involvement of neutrophils and its activator tumor necrosis factor (TNF) have been discussed. Here, we report a case of PCAS that was successfully treated with adalimumab, a human anti‐TNF monoclonal antibody. This is the first Asian case of PCAS that was improved by a TNF inhibitor.